Blindness and visual impairment due to age-related cataract in sub-Saharan Africa: a systematic review of recent population-based studies. Issue 10 (21st May 2013) - Bastawrous, Andrew; Dean, William H; Sherwin, Justin C
Abstract : Aim: We aimed to evaluate age-related cataract as a contributor to blindness and visual impairment (VI) in sub-Saharan Africa (SSA). Methods: A systematic review of population-based studies published between 2000 and October 2012. Prevalence and proportions of blindness and VI due to cataract, cataract surgical coverage (CSC), per cent intraocular lens (IOL) implantation and visual outcomes of surgery in accordance with WHO criteria were ascertained. Results: Data from 17 surveys (subjects mostly aged ≥50-years-old) from 15 different countries in SSA were included, comprising 96 402 people. Prevalence of blindness (presenting visual acuity <3/60 in better eye) ranged from 0.1% in Uganda to 9.0% in Eritrea, and the proportion of total blindness due to cataract ranged between 21% and 67%. Cataract was the principal cause of blindness and VI in 15 and 14 studies, respectively. There was a strong positive correlation between good visual outcomes and IOL use (R=0.69, p=0.027). Considerable inter-study heterogeneity was evident in CSC and visual outcomes following surgery, and between 40% and 100% of operations had used IOL. Conclusions: Cataract represents the principal cause of blindness and VI and should remain a priority objective for eye care in SSA. However, the prevalence of blindness and VI due to cataract was variable and may reflect differences in the availability of cataract surgical programmes and cataract incidence.